2012
DOI: 10.1556/achrom.24.2012.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of nine flavonoids in beagle dog by HPLC with DAD and application ofGinkgo bilobaextracts on the pharmacokinetic

Abstract: Summary. The method of high-performance liquid chromatography (HPLC) with diode array detector (DAD) was used and validated for the simultaneous determination of nine flavonoids (rutin, myricetin, quercitrin, quercetin, luteolin, genistein, kaempferol, apigenin, and isorhamnetin) in beagle dog plasma. Plasma sample was pre-treated with acetonitrile (containing 0.05% formic acid). Chromatographic separation was performed on a kromasil C 18 column (250 × 4.6 mm, 5 μm) maintained at 35 °C. The mobile phase was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…The elimination half-life (t 1/2β :0.250.03 h) of Quercetin in rats following single dose intramuscular administration in present study was found lower than reported following intravenous administration as 1.85 h (Khaled et al, 2003) and 3.84 h (Tang et al, 2009) in rats, 1.92 ± 0.62 h in rabbit (Liu et al, 2011) and 3.72 h in dogs (Wu et al, 2012). Whereas, very longer elimination half-life of 36.45± 14.08 h (Yang et al, 2013), 17.70 ± 3.70 h (Erlund et al, 2000) and 13.60±14.09 h in rats (Dong et al, 2017) and 11.90 ± 4.00 h in human (Graefe et al, 2001)has been reported following oral administration.…”
Section: Resultscontrasting
confidence: 63%
See 2 more Smart Citations
“…The elimination half-life (t 1/2β :0.250.03 h) of Quercetin in rats following single dose intramuscular administration in present study was found lower than reported following intravenous administration as 1.85 h (Khaled et al, 2003) and 3.84 h (Tang et al, 2009) in rats, 1.92 ± 0.62 h in rabbit (Liu et al, 2011) and 3.72 h in dogs (Wu et al, 2012). Whereas, very longer elimination half-life of 36.45± 14.08 h (Yang et al, 2013), 17.70 ± 3.70 h (Erlund et al, 2000) and 13.60±14.09 h in rats (Dong et al, 2017) and 11.90 ± 4.00 h in human (Graefe et al, 2001)has been reported following oral administration.…”
Section: Resultscontrasting
confidence: 63%
“…Whereas, very longer elimination half-life of 36.45± 14.08 h (Yang et al, 2013), 17.70 ± 3.70 h (Erlund et al, 2000) and 13.60±14.09 h in rats (Dong et al, 2017) and 11.90 ± 4.00 h in human (Graefe et al, 2001)has been reported following oral administration. The apparent volume of distribution (Vd (area) : 132.9224.14 L/kg) of Quercetin following single dose intramuscular administration in rats was found very higher than found 1.16 L/kg in rats (Khaled et al, 2003) and 21.63 L/kg in dogs (Wu et al, 2012) following intravenous administration. Whereas, very low apparent volume of distribution of 14.96  4.44 L/kg (Luo et al, 2016) and 71.70 L/kg (Khaled et al, 2003) in rats following oral administration have been reported.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The HPLC analysis of DLEE was performed on a HPLC (Agilent Tecnologies, Santa Clara, CA, USA) using a reversed-phase C18 (250 mm × 4.6 mm, 5 µm) column. The flavonoid compounds (resveratrol, rutin, quercetin, quercitrin, catechin, luteolin, apigenin, hesperetin, and hesperidin) were analyzed using gradient conditions [ 52 ]. The mobile phase composition was established with 0.2% formic acid in water (mobile phase A) and 100% methanol (mobile phase B), initially set at 70% A: 30% B at 0 min.…”
Section: Methodsmentioning
confidence: 99%